Impact of metal and plastic stents on endoscopic ultrasound-guided aspiration cytology and core histology of head of pancreas masses - Bekkali, Noor L. H.; Nayar, Manu K.; Leeds, John S.; Thornton, Lucy; Johnson, Sarah J.; Haugk, Beate; Darné, Antony; Howard-Tripp, Nadia; Charnley, Richard M.; Bassett, Paul; Oppong, Kofi W. (Endoscopy, 2019)
Background Stents are frequently placed in patients with biliary obstruction due to a mass in the head of the pancreas. The impact of plastic or self-expandable metal stents (SEMSs) on endoscopic ultrasound (EUS)-guided tissue sampling is unclear. This study aimed to assess, using strict pathological criteria, whether stents impair fine-needle aspiration (FNA) or fine-needle biopsy (FNB).Methods All patients with a solid mass in the head of the pancreas who underwent EUS-guided tissue sampling between 2010 and 2016 at our unit were included. Factors with possible impact on diagnostic performance were analyzed using logistic regression. Analysis was performed using both strict (malignant only) and less strict (suspicious for malignancy) cutoffs.Results Of 631 individuals undergoing 698 procedures, 535 (84.8 %) had a final diagnosis of malignancy, 141 had SEMS, 149 had plastic stents, and 341 had no stent. Using strict criteria, SEMS were associated with an increased occurrence of incorrect diagnosis of EUS tissue sampling, with an odds ratio (OR) of 1.96 (95 % confidence interval [CI] 1.24 – 3.10). Increasing tumor size (OR 0.72, 95 %CI 0.59 – 0.87), increasing number of passes (OR 0.84, 95 %CI 0.72 – 0.99), and fork-tip biopsy needle (OR 0.52, 95 %CI 0.31 – 0.86) were independently associated with a decrease in incorrect diagnosis. Repeat tissue sampling was more common with SEMSs (10.2 %) than with plastic stents (2.9 %) or no stents (4.5 %) (P < 0.02).Conclusion SEMS use had a negative impact on tissue diagnosis in pancreatic head masses, whereas use of a fork-tip biopsy needle and increasing number of passes were independently associated with improved accuracy.